2018
DOI: 10.1007/s10797-018-9502-7
|View full text |Cite
|
Sign up to set email alerts
|

Financial constraints and firm tax evasion

Abstract: Most analyses of tax evasion examine individual behavior, not rm behavior, given obvious and recognized data issues. We use data from the Business Environment and Enterprise Performance Survey to examine tax evasion at the rm level, focusing on a novel determinant of rm tax evasion: the nancial constraints (or credit constraints) faced by the rm. Our empirical results indicate across a range of alternative specications that more nancially constrained rms are more likely to be involved in tax evasion activities… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
52
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(58 citation statements)
references
References 57 publications
5
52
0
1
Order By: Relevance
“…Moreover, other findings [13] suggests that at an international level, tax compliance is related to bureaucracy (inverse relationship) and to the successful control of corruption (positive relationship). Also, there is suggestive evidence [2] that corruption (bribes) increase where there can be found opportunities for tax evasion activities.Also, more corruption enables the existence of more tax evasion, as some studies concluded [3].…”
Section: Problem Statementmentioning
confidence: 99%
“…Moreover, other findings [13] suggests that at an international level, tax compliance is related to bureaucracy (inverse relationship) and to the successful control of corruption (positive relationship). Also, there is suggestive evidence [2] that corruption (bribes) increase where there can be found opportunities for tax evasion activities.Also, more corruption enables the existence of more tax evasion, as some studies concluded [3].…”
Section: Problem Statementmentioning
confidence: 99%
“…"Economic policy" sets the following objectives in the area of tax administration: Simplify tax legislation, to amend parts of tax laws that allow ambiguous interpretation [2], simplify the tax system, reduce direct taxes, shift from direct taxes to indirect taxes in appropriate cases, reassess property tax rates, unify income tax rates, analyze the possibility of introducing an equal tax, strengthen tax revenues of municipalities, set tax revenues of the higher territorial units, ensure strict, direct, fair and effective tax collection, reduce tax evasion [44,45] and create a new system of horizontal financial equalization [39,46].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Against this background, corporate taxation increases the cost of capital and limits corporate investment. Hence, tax avoidance might also spur investment and produce some benefits for the economy as well (see Gravelle, 2013), particularly in the case of financial constraints (Alm et al, 2019). This other aspect is generally not accounted for in studies assessing the extent of BEPS.…”
Section: Introductionmentioning
confidence: 99%